Analysis of Village Funds Financial Management Planning in Air Dingin Village in Kaur District - Neri Susanti; Rinto Noviantoro; Ali Imran (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this research is to find out how the financial management planning in the Air Dingin Village of Kaur Regency and whether the village financial management plan in the Air Dingin Village of Kaur Regency is in accordance with the village financial management plan according to the Minister of Home Affairs Regulation number 113 of 2014. The data collection method uses a questionnaire and documentation and the data analysis method used is the analysis method used, which is to compare the Financial Management Planning Process made by the Air Dingin Village of Kaur Regency with the Minister of Home Affairs Regulation number 113 of 2014. The results of this study are the process of financial management planning Village Fund Allocation in the Air Dingin Village begins with the preparation of the RPJMDesa, RKPDesa and APBDesa. In general, the financial management planning process of Village Fund Allocation (ADD) in Desa Air Dingin has been in accordance with Permendagri number 113 of 2014. However, there is one article or provision that has not been implemented, namely article 20 paragraph 4 " in paragraph (3), namely the draft Village Regulation on APBDesa as referred to in article (2), namely the village secretariat submits the draft Village regulation on APBDesa to the Village Head and submitted by the village head to the Village Consultative Body for discussion and mutual agreement no later than in October of the year walk". however, for Desa Air Dingin it cannot be carried out in October 2018 but on March 18, 2019.